2011
DOI: 10.1111/j.1365-2621.2011.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boiling and microwaving treatments on nutritional characteristics and antioxidant activities of Agaricus blazei Murril

Abstract: The effects of boiling and microwaving on nutritional compositions, antioxidant components and antioxidant activities of fresh and frozen A. blazei Murril (AbM) were evaluated and compared. The results showed that the contents of crude protein, ash, total soluble protein, total soluble sugar, vitamin C, and total phenolics decreased by both cooking treatments, but no significant changes were observed in lipids. Amino acid composition analysis showed that the ratio of total essential amino acids to total amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
3
22
0
5
Order By: Relevance
“…However, the effect of microwaving on total soluble protein was significantly higher than that of boiling. Our study were in good agreement with the results Sun et al (2011), which suggested that heat treatment could significantly reduced the total sugars and proteins contents in Agaricus blazei Murril. It could be explained that some soluble sugars and proteins in FBTL were diffused from tissue to peripheral water.…”
Section: Effects Of Thermal Processing On Chemical Componentssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the effect of microwaving on total soluble protein was significantly higher than that of boiling. Our study were in good agreement with the results Sun et al (2011), which suggested that heat treatment could significantly reduced the total sugars and proteins contents in Agaricus blazei Murril. It could be explained that some soluble sugars and proteins in FBTL were diffused from tissue to peripheral water.…”
Section: Effects Of Thermal Processing On Chemical Componentssupporting
confidence: 92%
“…Total soluble protein and sugar were extracted and analyzed as Sun et al with some modifications (Sun et al, 2011). Samples (100 mg) were polished, homogenized after adding 5 mL PBS (50 mM, pH 7.8), then were centrifuged at 10,000 rpm at 4ºC for 15 min.…”
Section: Total Soluble Protein and Sugar Determinationmentioning
confidence: 99%
“…Foi encontrado valor de 2,55 mg de fenólicos totais/g de extrato de cogumelo-do-sol utilizando solvente metanol 50% com tempo de extração de 24 horas à temperatura ambiente (Sun et al, 2011), enquanto, com o solvente metanol 70% no mesmo tempo de extração (24 horas) à temperatura ambiente, foram achados valores de 0,83 a 42,21 mg de fenólicos totais/g de extrato para diferentes cogumelos comestíveis (Pleurotus porrigens, Hygrocybe conica, Xerula furfuracea, Schizophyllum commune, Polyporus tenuiculus e Pleurotus florida), representando oscilação bastante acentuada, conforme cada tipo de cogumelo avaliado (Wong;Chye, 2009).…”
Section: Resultsunclassified
“…Dessa forma, tendo em vista essa temperatura de extração, o valor mais baixo do IC 50 foi para o tempo de 60 min (15,80 mg mL -1 ). Nessas condições a atividade antioxidante aumentou com a elevação da temperatura de extração de 50º para 70ºC, diferindo de outros trabalhos, em que o tratamento térmico reduziu a quantidade de fenólicos totais, bem como alterou os tipos e a quantidade relativa desses compostos (Sun et al, 2011). Entretanto, esta pesquisa corrobora com resultados de outros estudos, que determinaram a temperatura de 70ºC como o limite máximo a ser empregado no processo extrativo para evitar a degradação, a polimerização e a oxidação de compostos fenólicos, fatores que resultariam na redução destes (Peixoto Sobrinho et al, 2010).…”
Section: Resultsunclassified
See 1 more Smart Citation